Pembentukan Nilai-Nilai Keagamaan pada Anak Usia Dini di TKIT Qurrota A’yun: Perspektif Psikologi Agama - Julya Julya; Noor Azida Batubara; Thariq Abidurrahman; Najwa Azizah; Abdul Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Islamic education in institutions such as TKIT Qurrota A'yun plays an irreplaceable role in shaping a deep understanding and appreciation of Islamic values in the early years of the younger generation. Since its establishment in 2007, TKIT Qurrota A'yun has become the heart that breathes sincere religious values into its students. However, amid various challenges that arise in the process of teaching Islam, these challenges have had a significant impact on children's understanding and acceptance of religion, indicating the need for a comprehensive approach rooted in religious psychology to provide deep and sustainable insights. In a theoretical framework, religious psychology emerges as a crucial foundation that helps understand how individuals acquire and apply religious understanding in their daily lives. Religious psychology theories such as Kohlberg's moral development theory, Piaget's cognitive theory, and Vygotsky's social theory provide in-depth perspectives on how children understand religious doctrines and their impact on Islamic religious education. Recent studies, such as Smith's (2019) study on religious psychology in the context of religious education, highlight the importance of a deep understanding of how religious understanding influences children's development process. The purpose of this article is to analyze in depth the influence of religious understanding and doctrine on education.